Analysis on the difference of time and space allocation of slots at regional hub airports: A Comparative Case Study of CTU and CKG. (October 2020) - Peiwen, Zhang; Fumin, Du; Tong, Chen; Yidan, Wu
Abstract: Taking Chengdu Shuangliu(CTU) and Chongqing Jiangbei(CKG) as examples, using flight data with methods such as volatility and external connection degree, the difference in slots allocation between adjacent regional hub airports from the time and space dimensions is quantitatively depicted. It shows that the overall flight schedule of CTU and CKG is similar, but during peak hours, the strong passenger demand of CTU Airport makes its flight volume more stable, moreover CKG enters the peak hour one hour later than CTU. The morning and evening peak-shaped flight waves are formed in both airports, but the take-off and landing intervals of CTU during peak hours are shorter than that of CKG. In addition, the take-off peak period of CKG is shorter than that of CTU; those with high external connections between the two airports are provincial capitals or sub-provincial cities in domestic, although some cities in remote provinces are more inclined to connect to CTU. International cities with higher external connections are all over China, especially nearly half of the international flights from both cities are to Southeast Asia, and connection degree between CTU and Southeast Asia is higher than Chongqing.